Metoda wagowego doboru przesunięcia fazowego do synchronizacji danych pomiarowych = Method of weighted selection of the phase shift for synchronization of measurement data - Warda, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The phase shift between waveforms is caused by various reasons. It can be both useful and redundant information. The phase shift value between the signals is one of the reasons that has a significant effect on the correct comparison of the instantaneous signals values.
Keywords: systemy pomiarowe